Naming streets after artists strengthens an effort of Bandung creative city branding - Allesandro, Yanuar Aldi; Fathinah, Alya; Nuraini, Nisrina; Rahmatika, Chaerunnisa; Herawati, Irna; Aunillah Sirait, Rinda (PRofesi Humas, 2025)
Background: Streets in Bandung are predominantly named after heroes and military figures, and none of them are named after artists despite Bandung’s branding as a Creative City. Purpose: This study aimed to map community readiness in Bandung, through the representation of the pentahelix stakeholders, to assess the feasibility of using artists’ names for street names. This community readiness was then analyzed in correlation to the city branding indicator, the City Branding Hexagon by Anholt (2007). Methods: The study used a descriptive qualitative method with Focus Group Discussion (FGD) for the primary data collection and a literature study for the secondary data. FGDs were conducted with ten participants from Pentahelix stakeholders (academics, government, business entities and/or actors, society or community, and mass media) who represented the people of Bandung City. Data validity checking was conducted through in-depth interviews with socio-economic experts. Results: The idea of naming artists as street names was welcomed by the majority of the Pentahelix elements who became informants in this study. The three artists who received support to be named as street names were Udjo Ngalagena, Harry Roesli, and Barli Sasmitawinata. The idea of naming artists as street names can strengthen the city branding of Bandung as a Creative City, which potentially improves the city’s economy, especially from the tourism aspect. Conclusion: Naming streets after artists in Bandung City could arouse the local artistic and cultural scene, which can be exploited to generate a creative platform to enhance the city’s artistic treasures and fortify Bandung City’s reputation as a creative hub. Implications: The implications of naming Harry Roesli as a street name arise. The location of Harry Roesli Music House is on a street that is the name of a national hero. For this reason, embedding Harry Roesli’s name needs to go through a special approach or determine a new location outside of his artistic site.